Transforming corporate governance and developing models for board effectiveness - Yasser, Qaiser Rafique, 1983-; Al-Manum, Abdullah, 1984- (Business Science Reference, 2021)
"With corporate governance as the system by which companies are directed and controlled, this book discusses different theories for boards of directors that are responsible for the governance of their companies and their practices around the globe"--